Implementation of Project Base-Learning in Improving Critical Thinking Skills in Early Childhood - Hatuwe, Okta Sulistiyo Rina; Syobah, Sy. Nurul; Idris, Husni (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This study investigates the implementation of Project-Based Learning (PBL) as a means to improve critical thinking skills in early childhood. The research was conducted at Nurul Hikmah Integrated Islamic Kindergarten (TKIT) and Handayani III Kindergarten (TK) in Penajam Paser Utara District, with the aim of supporting the implementation of the independent curriculum. This study uses a qualitative research design, using data collection techniques such as interviews, observations, and document studies. while data collection techniques are carried out by condensing data, displaying data, and drawing conclusions. The research findings show that PBL has proven to be an effective approach in improving early childhood critical thinking skills. Through the implementation of carefully planned PBL activities, children showed significant progress in their ability to identify problems, generate creative solutions, and consider different perspectives. In addition, PBL encourages the development of social skills, collaboration and creativity through teamwork and group discussions. Based on the research findings, it is recommended that the implementation of PBL in early childhood education follows a structured process. This includes defining clear learning objectives, selecting interesting and relevant project topics, setting realistic time frames, defining assessment criteria, providing necessary materials and resources, and offering guidance and support throughout the learning process. This research contributes to the existing literature by providing insights into the effective implementation of PBL to enhance critical thinking skills in early childhood education. The findings underscore the importance of well-structured planning, implementation, and evaluation to maximize the benefits of PBL. Further research is encouraged to explore additional factors and strategies that can further improve PBL implementation and outcomes in early childhood education settings. This study also identified several supporting factors that influence the successful implementation of PBL, including: the presence of creative and visionary teachers, a conducive learning environment, relevant learning content and the availability of resources. Conversely, inhibiting factors such as limited support from families, rigid curriculum constraints, limited resources and time constraints were also recognized.